2019
DOI: 10.3389/fimmu.2019.00174
|View full text |Cite
|
Sign up to set email alerts
|

PRMT5 Associates With the FOXP3 Homomer and When Disabled Enhances Targeted p185erbB2/neu Tumor Immunotherapy

Abstract: Regulatory T cells (Tregs) are a subpopulation of T cells that are specialized in suppressing immune responses. Here we show that the arginine methyl transferase protein PRMT5 can complex with FOXP3 transcription factors in Tregs. Mice with conditional knock out (cKO) of PRMT5 expression in Tregs develop severe scurfy-like autoimmunity. In these PRMT5 cKO mice, the spleen has reduced numbers of Tregs, but normal numbers of Tregs are found in the peripheral lymph nodes. These peripheral Tregs that lack PRMT5, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 61 publications
1
65
0
Order By: Relevance
“…We previously reported that the deletion of PRMT5 in Treg cells leads to their defective peripheral maintenance and function, causing a lethal scurfy-like phenotype in Foxp3 Creyfp PRMT5 fl/fl mice within 4 wk of age. We found that PRMT5 symmetrically di-methylates Foxp3 at arginine 51 and that a point mutation of arginine 51 to lysine on Foxp3 leads to defective Treg function (11). However, taking our current results into consideration, the defective maintenance, activation, and proliferation of PRMT5-deficient Foxp3 + Treg cells may also be attributed to impaired γc signaling.…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations
“…We previously reported that the deletion of PRMT5 in Treg cells leads to their defective peripheral maintenance and function, causing a lethal scurfy-like phenotype in Foxp3 Creyfp PRMT5 fl/fl mice within 4 wk of age. We found that PRMT5 symmetrically di-methylates Foxp3 at arginine 51 and that a point mutation of arginine 51 to lysine on Foxp3 leads to defective Treg function (11). However, taking our current results into consideration, the defective maintenance, activation, and proliferation of PRMT5-deficient Foxp3 + Treg cells may also be attributed to impaired γc signaling.…”
Section: Discussionmentioning
confidence: 44%
“…This led to the development of PRMT5 inhibitors for cancer therapy and some are under clinical trials (24). We previously demonstrated that PRMT5 inhibition by DS-437 enhances anti-tumor effects of anti-erbB2/neu monoclonal antibody targeted therapy in a drug-resistant syngeneic murine breast cancer model by inhibiting Treg function and induction of tumor immunity (11). However, our current study revealed that PRMT5 is also important for conventional T cell responses.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Conditional knock‐out of the PRMT5 gene in T regs causes severe Scurfy‐like autoimmunity. Consistently, pharmacological ablation of PRMT5 activity by DS‐437 also reduces human T reg functions, which enhance the anti‐tumor effects of anti‐erbB2/ neu monoclonal antibody‐targeted therapy in mice bearing CT26 human epidermal growth factor receptor (HER2) tumors .…”
Section: Post‐translational Modifications Of Foxp3mentioning
confidence: 84%